2016
DOI: 10.1097/mpg.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activity of Colostrum and Human Milk

Abstract: Pasteurization and storage affect nonenzymatic and enzymatic antioxidative agents in human milk. It appears that nonenzymatic antioxidative systems in colostrum and milk are different. The effects of processing may be partially compensated by fortification/spiking with ascorbate before use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 49 publications
2
35
0
1
Order By: Relevance
“…For this reason, we included mothers who had delivered before 34 weeks' gestation in the study. Similar to previous studies, [33][34][35] we found that colostrum has the highest TAC level which decreased in the later stages of lactation. However, decrease in TAC was not statistically significant in preterm BM.…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, we included mothers who had delivered before 34 weeks' gestation in the study. Similar to previous studies, [33][34][35] we found that colostrum has the highest TAC level which decreased in the later stages of lactation. However, decrease in TAC was not statistically significant in preterm BM.…”
Section: Discussionsupporting
confidence: 91%
“…Colostrum is essential in the antioxidant mechanism of the newborn [56][57][58][59] and our results demonstrate, the antioxidant potential of CCM exosomes on canine fibroblast.…”
Section: Exosomes Play a Key Role In Cell-to-cell Communication And Cmentioning
confidence: 58%
“…Transitional milk is thinner, watery and sweeter, compared to colostrum. Compared with colostrum and mature milk of mothers of preterm infants, transitional milk has lower ORP value indicating better TAC than colostrum or mature milk. Breast milk from mothers of preterm infants of 29–34 gestation weeks, collected up to 40 weeks of postnatal age showed a temporal change over the first 3 weeks of lactation, approaching zero with the achievement of term age .…”
Section: Discussionmentioning
confidence: 92%